The canons of the Third Lateran Council of 1179 their origins and reception - Summerlin, Danica ca. 20./21. Jh. (Cambridge New York, NY Port Melbourne New Delhi Singapore Cambridge University Press, 2021)
"Ecclesiastical councils present a peculiar problem for historians of the medieval church, and especially for those trying to understand the nature of medieval papal authority. Despite an ancient pedigree, the pre-eminence of ecclesiastical councils began to fade over the course of the central middle ages"--
Alexander III's 1179 Lateran Council, was, for medieval contemporaries, the first of the great papal councils of the central Middle Ages. Gathered to demonstrate the renewed unity of the Latin Church, it brought together hundreds of bishops and other ecclesiastical dignitaries to discuss and debate the laws and problems that faced that church. In this evaluation of the 1179 conciliar decrees, Danica Summerlin demonstrates how these decrees, often characterised as widespread and effective ecclesiastical legislation, emerged from local disputes which were then subjected to a period of sifting and gradual integration into the local and scholarly consciousness, in exactly the same way as other contemporary legal texts. Rather than papal mandates that were automatically observed as a result of their inherent papal authority, therefore, Summerlin reveals how conciliar decrees should be viewed as representative of contemporary discussions between the papacy, their representatives and local bishops, clerics, and scholars.
Literaturverzeichnis: Seite 261-295
Keywords: Catholic Church -- History of doctrines -- Middle Ages, 600-1500; Church History -- Middle Ages, 600-1500